Digital Storytelling in Early Childhood: Student Illustrations Shaping Social Interactions - O’Byrne, William Ian; Houser, Katherine; Stone, Ryan; White, Mary (Frontiers in Psychology, 2018)
This study tests an instructional model designed to empower students in an early childhood classroom as emerging digital storytellers. Educators can use digital storytelling to support students’ learning by encouraging them to organize and express their ideas and knowledge in an individual and meaningful way while developing voice and facility in child-computer interactions. This work also helps develop traditional communication skills, fosters collaboration, and strengthens emergent literacy practices. Students may develop enhanced communications skills by learning to organize their ideas, ask questions, express opinions, and construct narratives as they interact with others and computers in the creation of digital stories. The “Emerging Digital Storytellers” instructional model focuses on social-emotional development and finding student voice through writing and digital content construction in the early childhood educational context